Heterogeneity in the effect of different ixodid tick species on human natural killer cell activity. - Kubes, M; Kocáková, P; Slovák, M; Sláviková, M; Fuchsberger, N; Nuttall, P (2002)
Tick saliva plays a vital role in blood-feeding, including manipulation of the host response to tick infestation. Furthermore, a diverse number of tick-borne pathogens are transmitted to vertebrate hosts via tick saliva, some of which exploit the immunomodulatory activities of their vector's saliva. We report that salivary gland extracts (SGE) derived from Dermacentor reticulatus adult ticks induce a decrease in the natural killer (NK) activity of effector cells obtained from healthy human blood donors. The decrease was observed with SGE from both female and male D. reticulatus fed for either 3 or 5 days on mice, but no significant effect was observed with SGE from unfed ticks or ticks that had fed for 1 day. These results indicate that the tick anti-NK factor(s) is only active after blood-feeding has commenced. Microscopic examination revealed that the first step of NK activity, namely effector/target cell conjugate formation, was affected by SGE. The observed reduction in conjugate formation occurred when effector (but not target) cells were treated with SGE for 30 min, and the effect persisted after 12 h of treatment. Similar but less potent anti-NK activity was detected for SGE from Amblyomma variegatum and Haemaphysalis inermis. By contrast, SGE derived from Ixodes ricinus and Rhipicephalus appendiculatus female ticks did not decrease NK activity. The apparent absence of such activity in these two important vectors of tick-borne viruses suggests that control of NK cells does not play an important role in promoting virus transmission, at least for these particular species.